Studi Eksperimental Kuat Tekan Beton Geopolimer dengan Metode Curing Pembasahan - Desimaliana, Erma (Civil Infrastructure Engineering and Architectural Design, 2025)
Geopolymer concrete is an environmentally friendly concrete that does not use cement at all, but uses high silica-containing materials such as fly ash (waste from PLTU). Geopolymer concrete consists of a binder material in the form of fly ash reacted with an alkaline activator solution, and filler material in the form of aggregate. The alkaline activator used is a solution of NaOH concentration of 8M and Na2SiO3 solution in a ratio of 1:2, while the ratio of aggregate and binder is 60%: 40%. In this study, the wetting treatment method was carried out with the number of test specimens for each variation as many as 3 test specimens and concrete compressive strength testing was carried out at the age of 3, 7, and 28 days on cylindrical test specimens with a size of 10 cm × 20 cm as many as 9 test specimens. Based on the results of the compressive strength test, the relationship graph between the compressive strength of concrete and the age of concrete is obtained, the value of the compressive strength of concrete with the wetting treatment method is 19.92 MPa